Singapore women and fitness : an analysis of attitudes and media. - Lau, Evelyn Lai Yee. (2008)
In response to the emerging social and govermental consciousness towards health and fitness, this exploratory study aims to examine the content of beauty and fitness related Singapore maganizes to find out if there is a relationship between fitness portrayal in the ads and Singaporean women's participation in physical fitness activities.